2022
DOI: 10.1111/ejn.15650
|View full text |Cite
|
Sign up to set email alerts
|

microRNA expression levels in the nucleus accumbens correlate with morphine‐taking but not morphine‐seeking behaviour in male rats

Abstract: A powerful motivation to seek opioids remains after drug cessation and intensifies during extended periods of abstinence. Unfortunately, biomarkers associated with continued drug seeking have not been described. Moreover, previous studies have focused on the effects of early abstinence with little exploration into the long-term drug-induced mechanisms that occur after extended abstinence. Here we demonstrated that 30 days (D) of forced abstinence results in a time-dependent increase in morphine seeking in a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Chronic morphine exposure could induce drug addiction and affect brain functions [21][22][23][24]. As we all know, withdrawal is a part of morphine addiction, this uncomfortable syndrome occurs after morphine discontinued and it was also the major reason of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic morphine exposure could induce drug addiction and affect brain functions [21][22][23][24]. As we all know, withdrawal is a part of morphine addiction, this uncomfortable syndrome occurs after morphine discontinued and it was also the major reason of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…The regions of the OFC dissected were the ventral OFC and lateral OFC subregions. For extraction of total RNA from OFC tissue, the miRVANA PARIS RNA extraction kit (Life Technologies, Carlsbad, CA) was used, as we have previously reported [ 7 , 24 , 34 ]. Exosomal RNA was extracted from blood serum using the SeraMir Exosome RNA Amplification Kit (System Biosciences, Palo Alto, CA), according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Because of this, miRNA-mediated inhibition of protein translation is an essential regulatory mechanism for modulation of gene expression and the proteome [ 11 ]. Exposure to all classes of drugs can induce long-lasting alterations to brain miRNA expression profiles and regulation of miRNA function can modulate drug seeking behavior [ 7 , 12 24 ]. Manipulation of individual miRNA expression or functional capabilities has been reported to regulate seeking for the opioids morphine and heroin, as well as psychostimulants and alcohol [ 14 , 17 , 20 , 21 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs participate in the molecular pathways that modulate the behavioral phenotypes and the cellular neuroadaptations induced by opioid exposure. A recent study conducted in a rat model of morphine self-administration identified several drug-responsive microRNAs in the NAcc and revealed that their lasting expression profiles correlate with morphine-taking but not morphine-seeking behavior in males, since the miRNA profile undergoes regulation from early to late abstinence [144]. Therefore, miRNA signature may represent a marker of past drug abuse.…”
Section: Epigenetic Mechanisms and Targets In Drug Addictionmentioning
confidence: 99%